2019
DOI: 10.9734/acri/2019/v16i230087
|View full text |Cite
|
Sign up to set email alerts
|

Food Handling Practices among Food Handlers of Eating Establishments in the Government Hospitals, Mandalay City, Myanmar

Abstract: Background: Hospital environment is a favourable condition for growing of pathogens. Unhygienic practices of food handlers and contaminated food may be the cause of foodborne diseases, resulting in much comorbidity and longer hospital stay of the affected persons. Aims: To study socio-demographic characteristics, working characteristics and food handling practices among food handlers of eating establishments in the government hospitals, Mandalay city, Myanmar. Study Design: Cross-sectional descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…There was no significant association between level of food handling practices and respondents' age group, monthly income, marital status, occupational status, type of delivery, and educational level. This was consistent with a similar study by Aung et al [ 28 ], where there was no significant association between the age group, income level, educational level, and food handling practice of the respondents. However, in the present study, there was an association between food handling practice and respondents' religion, ethnicity, place of residence, occupational status, and number of children.…”
Section: Resultssupporting
confidence: 93%
“…There was no significant association between level of food handling practices and respondents' age group, monthly income, marital status, occupational status, type of delivery, and educational level. This was consistent with a similar study by Aung et al [ 28 ], where there was no significant association between the age group, income level, educational level, and food handling practice of the respondents. However, in the present study, there was an association between food handling practice and respondents' religion, ethnicity, place of residence, occupational status, and number of children.…”
Section: Resultssupporting
confidence: 93%
“…Factors contributing to this could be the lack of training and poor inspection by authority. These findings were almost nearly agreed to the studies of Aung et al, andKhine Hsu Wai in Myanmar (Khine Hsu Wai, 2018, Aung et al, 2019). Therefore, although after some time, we found that there wasn't significant change in food safety practice in Myanmar.…”
Section: Chapter V Discussionsupporting
confidence: 89%
“…Contaminated water, poor food handling and food processing, and a lack of proper facilities of food storage have all been linked to the higher prevalence of these diseases in lowincome nations [12,13]. The sanitation habits of food handlers continue to be the most effective method for reducing foodborne disease outbreaks [6] [14].…”
Section: Introductionmentioning
confidence: 99%